2015
DOI: 10.1089/neu.2014.3471
|View full text |Cite
|
Sign up to set email alerts
|

Primary Blast-Induced Traumatic Brain Injury in Rats Leads to Increased Prion Protein in Plasma: A Potential Biomarker for Blast-Induced Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is deemed the ''signature injury'' of recent military conflicts in Afghanistan and Iraq, largely because of increased blast exposure. Injuries to the brain can often be misdiagnosed, leading to further complications in the future. Therefore, the use of protein biomarkers for the screening and diagnosis of TBI is urgently needed. In the present study, we have investigated the plasma levels of soluble cellular prion protein (PrPC) as a novel biomarker for the diagnosis of primary bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 75 publications
(76 reference statements)
1
16
0
Order By: Relevance
“…A recent study suggested a potential biomarker specific to blast TBI—soluble cellular prion protein (PrPC). The hypothesis is that the primary blast wave can dislodge any extracellular PrPC and lead to a systemic rise in its concentration 65. The hypothesis was demonstrable in rat models in a 2015 study and the authors concluded the PrPC could be a novel biomarker for detection of primary blast TBI in military personnel.…”
Section: Potential Role Of Tbi Biomarkersmentioning
confidence: 99%
“…A recent study suggested a potential biomarker specific to blast TBI—soluble cellular prion protein (PrPC). The hypothesis is that the primary blast wave can dislodge any extracellular PrPC and lead to a systemic rise in its concentration 65. The hypothesis was demonstrable in rat models in a 2015 study and the authors concluded the PrPC could be a novel biomarker for detection of primary blast TBI in military personnel.…”
Section: Potential Role Of Tbi Biomarkersmentioning
confidence: 99%
“…Because PrP c is located entirely within the extracellular domain of the plasma membrane, it is reasonable to suspect that it may be released during a concussive event through BBB disruption (33). Indeed, transcription of the prion protein gene (PRNP) is upregulated in a rat model of concussion following blast exposure, resulting in increased serum levels (34,35).…”
Section: Plasma-soluble Prion Protein Cellular Prion Protein (Prp Cmentioning
confidence: 99%
“…It has been shown that PrP C is increased in blood during TBI (Pham, Akonasu, Shishkin, & Taghibiglou, ; Pham, Sawyer, et al., ). Therefore, formation of PrP C aggregates in extravascular space during TBI can be a result of leaking of this plasma protein through the impaired vascular wall.…”
Section: Molecules Involved In Both Vascular and Non‐vascular Mediatementioning
confidence: 99%